Accented style : on Namewee’s Sinophone Malaysian film and rap songs - Hee, Wai-Siam (2020)
Focusing on Namewee’s rap songs and his film, this essay uses Sinophone theory and accented cinema theory to explore how sound and image are used to perform Sinophone identity through journeys of deterritorialization and reterritorialization. The essay demonstrates that Namewee’s works are neither a national allegory nor an exilic/diasporic allegory, and therefore that neither the perspective of national discourse nor diaspora discourse can adequately frame his works. Sinophone Malaysian accented cinema is an appropriate one from which to approach Namewee’s films. In the theoretical framework of accented cinema, Namewee is a postcolonial ethnic and identity filmmaker; in the Malaysian context he is “not quite” equal to Malays, and neither is he accepted or trusted as a full citizen. The accented style of Namewee’s works is intimately linked to localization, diaspora and against-diaspora experiences, and Chinese–Malay relations. He has successfully updated the understanding that accented style can only be produced from exile/diaspora experience, demonstrating that against-diaspora experience and localization can also create an accented style. This essay analyzes the re-presentation of Sino-Malay relations in Namewee’s works and discovers that they refuse to rely on the standard ethnic framework. Rather, the accented style of these works gives play to the multiply mediated, multidirectional critical agency of Sinophone theory: the Sinification discourse of “authenticity” is criticized, while at the same time a performance of national identities is used to resist the presence of racism and expose the essentialized Malay mythologization of indigeneity.